Analysis of Social And Religion Change of Dayak Ma'amp on Katipak Dance In The Ritual Babukokng - Audina, Sovi; Tindarika, Regaria; Aditya, Mega Cantik Putri (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
This study aims to explain the forms of social change and shifts in belief systems that occur within the Dayak Ma’amp community, as well as their relationship to the implementation of the Babukokng ritual and the continuity of the Katipak Dance as one of the sacred cultural elements. The focus of the research is directed toward identifying the forms of social and belief changes within the Dayak Ma’amp community, particularly those related to the practice of Babukokng and the preservation of the Katipak Dance. The study employs a qualitative approach with technique triangulation, which involves comparing data derived from interviews, observations, and document studies. Anthropological and historical approaches are used to understand how social and belief changes unfold within the Ma’amp community. The findings indicate that social change in the Ma’amp community can be seen through the shift from traditional customary leadership to a dual system involving village governance, the transition of livelihoods toward a monetary economy, and the simplification of the duration and procedures of the Babukokng ritual. The community’s belief system has also shifted due to the influence of formal religions, which have weakened traditional beliefs in spirits and spiritual elements, resulting in the modification or removal of certain ritual stages. The Katipak Dance, which was once strictly sacred, has undergone desanctification and can now be performed in public cultural events as an effort toward preservation. Overall, these changes demonstrate that the Ma’amp community is able to adapt to modern developments while simultaneously facing challenges in cultural regeneration if deliberate preservation efforts are not implemented.